Study on the behavior of cane wood fiber–reinforced polymer composites for application in design - Cornelius Ogbodo Anayo Agbo (Academia Materials Science)
The growing need for sustainable green products and green manufacturing has broadened the search for high-quality natural fibers to reinforce polymer composites. However, as composites continue to serve as a viable alternative to metals in many engineering designs, the proper evaluation of these materials’ suitability is essential to aid in predicting the in situ manufacturing possibilities and in-service conditions. Cane wood fiber–reinforced composites are characterized in this study using notable mechanical tests, including tensile, compression, flexural, and impact tests. Test samples were produced with various cane wood fiber compositions of 15%, 30%, and 50% by volume fiber content. Comparative data from the samples were generated to assess their strength and behavior. The results obtained showed that cane wood fiber–reinforced polyester resin achieved a maximum tensile strength of 9.58 N/mm2 at 15% by volume fiber content, exhibiting a brittle behavior. The maximum energy to break of 4.68 J and the maximum impact strength of 0.78 N/mm2 were obtained at 30% by volume fiber content. It is, therefore, evident that while the 15% volume fiber content is structurally more suitable, the 30% volume fiber content offers better impact and damping characteristics, making it more appropriate for upholstery works and interior trim parts.